Enantioselective Arylation of 3-Carboxamide Oxindoles with Quinone Monoimines and Synthesis of Chiral Spirooxindole-benzofuranones - Chen, Hui; Liu, Hui; Zhao, Si-Han; Cheng, Shao-Bing; Xu, Xiao-Ying; Yuan, Wei-Cheng; Zhang, Xiao-Mei (Synlett, 2019)
A highly enantioselective arylation of 3-carboxamide oxoindoles with quinone monoimines is described. Various 3-aryl-3-carboxamide oxindoles with an all-carbon quaternary center were obtained in moderate to good yields (up to 99%) with moderate to good enantioselectivities (up to 98%) in the presence of a bifunctional thiourea-tertiary amine catalyst. The absolute configuration of one product was determined by an X-ray crystal structural analysis and the absolute configurations of the other products can be assigned by analogy. Moreover, several chiral spirooxindole-benzofuranones were synthesized from the 3-aryl-3-carboxamide oxindoles in moderate yields with moderate to good enantioselectivities.
Keywords: arylation; 3-carboxamide oxindoles; quinone monoimines; 3,3-disubstitutied oxindoles; spirooxindoles-benzofuranones